A network perspective on the organisation of social housing in the Netherlands: The case of urban renewal in The Hague - van Bortel, Gerard; Elsinga, Marja (A+BE | Architecture and the Built Environment, 2016)
In the past 15 years Dutch housing associations have undergone a transformation from strictly regulated and heavily subsidized organisations to financially and administratively independent enterprises. This transformation has sparked a lively debate on regulation and the role of the government in social housing. There is a broad consensus that something needs to be done about the operations of housing associations in the Netherlands. Hence, their position and performance are a current topic of discussion in the Dutch Parliament. In this paper we examine public management from a network perspective. We envisage the policy environment as a network of players and explore three key concepts: ‘‘multiformity’’, ‘‘closedness’’ and ‘‘interdependence’’. The government is not the dominant party in this scenario, but one of several players with their own specific goals and resources. To be sure of a good performance, instruments of governance need to be in tune with the characteristics of the network. This paper discusses the instruments applied in the Dutch social housing network and uses the results of a case study in The Hague to illustrate the efficacy of the network perspective in social housing analyses and to highlight the strengths and weaknesses of the current governance structure.